2014
DOI: 10.1186/1756-9966-33-28
|View full text |Cite
|
Sign up to set email alerts
|

Baseline staging tests based on molecular subtype is necessary for newly diagnosed breast cancer

Abstract: BackgroundBone scanning (BS), liver ultrasonography (LUS), and chest radiography (CXR) are commonly recommended for baseline staging in patients with newly diagnosed breast cancer. The purpose of this study is to demonstrate whether these tests are indicated for specific patient subpopulation based on clinical staging and molecular subtype.MethodsA retrospective study on 5406 patients with newly diagnosed breast cancer was conducted to identify differences in occurrence of metastasis based on clinical staging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 34 publications
1
28
2
Order By: Relevance
“…A Chinese retrospective study with information on molecular subtype in 3,411 patients with stage I-III BC showed that luminal a, luminal b, luminal B plus Her2, Her2 overexpression, and basal-like have a statistically different risk for bone (1.4%, 0.7%, 2.5%, 2.7%, and 0.9% respectively; p < 0.05), liver (0.1%, 0.1%, 1.0%, 1.1%, and 0.9% respectively; p < 0.01) and lung metastases (0.2%, 0%, 0%, 0.27%, and 0.9% respectively; p < 0.05); however, the risk of occult metastases was generally low for all subtypes. 6 Conversely, we report a numerically, non-statistically significant higher rate of DM in Her2 positive and TN disease (6.4% in Her2 positive and HR positive; 5.9% in Her2 positive and HR negative, and 7.9% in TN). The lack of statistical significance could simply be due the small sample size for subgroup analyses.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…A Chinese retrospective study with information on molecular subtype in 3,411 patients with stage I-III BC showed that luminal a, luminal b, luminal B plus Her2, Her2 overexpression, and basal-like have a statistically different risk for bone (1.4%, 0.7%, 2.5%, 2.7%, and 0.9% respectively; p < 0.05), liver (0.1%, 0.1%, 1.0%, 1.1%, and 0.9% respectively; p < 0.01) and lung metastases (0.2%, 0%, 0%, 0.27%, and 0.9% respectively; p < 0.05); however, the risk of occult metastases was generally low for all subtypes. 6 Conversely, we report a numerically, non-statistically significant higher rate of DM in Her2 positive and TN disease (6.4% in Her2 positive and HR positive; 5.9% in Her2 positive and HR negative, and 7.9% in TN). The lack of statistical significance could simply be due the small sample size for subgroup analyses.…”
Section: Discussioncontrasting
confidence: 63%
“…1 Distant metastases (DMs) are found in $ 4% of newly-diagnosed patients with early breast cancer (EBC)-defined as stage I-II by the American Joint Committee on Cancer (AJCC) Cancer Staging Manual, Seventh Edition (2010) 2 -when they undergo imaging procedures for initial staging. 3 Because DMs are uncommon in this setting, [4][5][6][7] international guidelines advise against routine imaging of asymptomatic EBC patients. 8,9 The National Comprehensive Cancer Network (NCCN) only recommends imaging procedures in cases of EBC when guided by symptoms (such as bone, respiratory or abdominal pain), or laboratory abnormalities (such as elevated alkaline phosphatase, abnormal liver function), but recommends staging for all stage III patients 2 due to the higher prevalence of occult DMs in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and co‐workers have suggested that the decision for systemic staging could be based on the molecular subtype of the breast cancer rather than the clinical stage of disease. In their study, patients were staged with liver ultrasonography, chest X‐ray and bone scan.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of occult metastatic disease in patients with newly diagnosed breast cancer are low, estimated at between 5 and 7 per cent. The most common site of metastatic disease is bone followed by lung and liver. Traditionally, routine biochemistry, chest X‐ray, liver ultrasound examination and a bone scan were standard for systemic staging of breast cancer, but the overall identification of metastatic disease was low.…”
Section: Introductionmentioning
confidence: 99%
“…Ki67 was high in 34.4% and LVI was present in 24.2% of the patients. These parameters represent the new molecular classifications of breast cancer that not only allow to identify patients at a higher risk of relapse but may also guide postoperative therapies [10, 11]. Tumor size was divided in quartiles, the cut-offs being 12, 18 and 25 mm.…”
Section: Resultsmentioning
confidence: 99%